Relation between scales and factors of Arnett's Inventory of Sensation Seeking (AISS) in the sample of Croatian athletes - Vukosav, Željko; Bunjevac, Tomislav; Zolotić, Sanja Zarevski, Predrag (1997)
AISS (Arnett, 1994) was administered on a sample od 197 men, ranging in age from 17 to 47 years (M = 29, 6 years). The scale represents a new way of conceptualizing a sensation seeking construct. It consists of 20 items divided into two subscales, intensity and novelty, each containing 10 items. Relatively low reliability coefficients were found for the two subscales: Cronbach alpha for the novelty scale is .531, and for the intensity scale is .584. Subscales show relatively high correlations: r = 0.52. Only 3 items, concerning travels abroad and marriage to someone from a foreign country, have satisfactory correlations with a corrected total result for the novelty scale. For the intensity subscale 8 items have relatively balanced correlation coefficients, while the remaining 2 have zero correlation. Principal components and common factors analyses revealed highly congruent two-factor solutions (correlations for corresponding latent dimensions are over .97). The novelty scale correlates with the corresponding component r = .73, and with an intensity component r = .40. Intensity scale correlation with corresponding component is .75, and with the novelty component is .50. Higher relations between scales and factors could hardly be expected due to low internal consistency of the scales.
Projekt MZOS
ENG